An Analysis of Language Style Used in “The Princess Switch” Movie and Its Implications in Teaching Speaking - Lilian Salsabila; Pradnya Permanasari (Jurnal Lingua Idea, 2022)
This research aims to describe the types of language styles based on the level of formality theory by Joos in Sutherland (2016), identify the most frequent language used, and explain its implications in teaching speaking. The method used in this research was a descriptive qualitative method. The data was movie dialogues entitled "The Princess Switch". Data collection techniques used in this research were observation and documentation. The results of this research show 90 data from movie dialogues used in the movie. The writer concludes that there are five types of language styles used in this research, namely frozen style (1 datum), formal style (43 data), consultative (9 data), casual style (26 data), and intimate (11 data). The most frequently used language in the movie is the formal style type. In addition, this research can be used as alternative teaching materials and references for teachers and the government.